2001
DOI: 10.1002/app.2076
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of polyoxymethylene/montmorillonite nanocomposite

Abstract: ABSTRACT:The nonisothermal crystallization kinetics of polyoxymethylene (POM), polyoxymethylene/Na-montmorillonite (POM/Na-MMT), and polyoxymethylene/organic-montmorillonite (POM/organ-MMT) nanocomposites were investigated by differential scanning calorimetry at various cooling rates. The Avrami analysis modified by Jeziorny and a method developed by Mo were employed to describe the nonisothermal crystallization process of POM/Na-MMT and POM/organ-MMT nanocomposites. The difference in the values of the exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…At high supercooling, at temperatures slightly below about 100 °C, there is then observed a rapid increase of the crystallization rate due to a change from heterogeneous nucleation, evident at high temperature, to homogeneous nucleation, prevailing at low temperature. Note that the change of the nucleation mechanism on variation of the supercooling of the melt has been investigated in an independent study [21,22]. Most important in the context of the present work, however, is the observation of a decrease of the characteristic time of crystallization of PA 11 due to the presence of the nanofillers.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…At high supercooling, at temperatures slightly below about 100 °C, there is then observed a rapid increase of the crystallization rate due to a change from heterogeneous nucleation, evident at high temperature, to homogeneous nucleation, prevailing at low temperature. Note that the change of the nucleation mechanism on variation of the supercooling of the melt has been investigated in an independent study [21,22]. Most important in the context of the present work, however, is the observation of a decrease of the characteristic time of crystallization of PA 11 due to the presence of the nanofillers.…”
Section: Resultsmentioning
confidence: 80%
“…For many polymers including polypropylene [18][19][20], polyoxymethylene [21], poly(ethylene terephthalate) [22], poly(butylene terephthalate) [23], poly(butene-1) [24], but in particular polyamides [25][26][27][28][29][30][31][32][33][34], it has been shown that addition of nanofillers often enhance crystallization and even support the formation of specific crystal polymorphs. In fewer cases, however, a retardation of the crystallization process has also been reported, likely due to an immobilization of polymer chain segments at the polymer/nanofiller interface [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Compositing to the matrixes, not only the mechanical properties of materials prepared by this method are increased significantly, but the composite materials have many especial performance, such as thermal stability, magnetism, electricity and nonlinear optics and so on [17]. But, there are still some limitations in the application of this method, such as melt intercalation method, the nanoparticles are still difficult to be dispersed uniformly.…”
Section: Intercalation Compound Methodsmentioning
confidence: 99%
“…Furthermore, it exhibits low water absorption and good electrical insulation properties, rendering it as a perfect candidate for electrical and electronic applications [8]. On the other hand, the high degree of crystallinity of POM accompanied by brittleness is a limiting factor for its applications [9,10]. Blending POM with thermoplastic polyurethane (PU) is often proposed as a reliable solution for POM toughening [11][12][13].…”
Section: Introductionmentioning
confidence: 99%